Dimensional effects in thin gold films - Kovalenko, S.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Research results of optical constants of thin gold films of different thickness are given in the paper. Their structure was studied using atomic-force microscope. Values of refraction n and absorption k coefficients were calculated from reflection and transmission spectra by traditional ratios, and using new theory as well. Comparison of results obtained by both methods was carried out and possible causes of divergences were pointed out.